Natural Indicator as a substitute to Synthetic indicator-A Developmental Approach - Chinmoy Paul, Debarupa D. Chakraborty, Amitava Ghosh, Prithviraj Chakraborty (Journal of Applied Pharmaceutical Science, 2014)
Synthetic indicators had perpetually been an alternative choice for all types of titration since long time. However price had always been a tangle. Therefore development of an indicator from natural source i.e. from the flower extracts had been the main aim of this present research work. The current work complies data regarding the comparison of Natural indicator and synthetic indicator and whether or not it may be substituted from Synthetic indicator.
Keywords: Impatiens, Indicator, Phenolphthalein, methyl orange, methyl red.